EXAFS studies under high pressure by X-ray Raman scattering. Issue 3 (2nd July 2016) - Hiraoka, N.; Fukui, H.; Okuchi, T.
ABSTRACT: We discuss extended X-ray absorption fine structure (EXAFS) measurements on light element compounds under high pressure. An absorption edge in light elements, ≤2 keV in energy, is measured by X-ray Raman scattering using 20 keV X-rays. To enhance the intensity, a large-culet, sintered polycrystalline diamond anvil cell is used, so that a scattering volume is maximized. For a pressure monitor, diffraction lines from NaCl powders compressed together with the sample are measured through an X-ray Raman spectrometer. With this set-up, we have measured EXAFS features at the oxygen K -edge in MgSiO 3 glass up to 30 GPa. As the pressure increases, the oscillation pattern drastically changes, associated with the densification of the glass.